THU0488-HPR Health care utilization in patients with systemic sclerosis. (23rd January 2014) - Willems, L.; Kwakkenbos, L.; Bode, C.; van den Hoogen, F.H.; van den Ende, E.H.
Abstract : Background: Systemic sclerosis (scleroderma, SSc) is a rare and complex connective-tissue disease with heterogeneous manifestations. The disease has a large impact on functioning and quality of life in the majority of patients [1]. No effective treatment is available yet. In addition to medical treatment, non-pharmacological treatment is often provided, with the aim to support patients in living with the consequences of the disease. So far, little is known about the amount and diversity of health care services use by SSc patients. Studying health care utilization might help improve and optimize care of patients with SSc. Objectives: To assess health care utilization in SSc. Methods: In 2011, the Dutch patient association for patients with systemic autoimmune diseases contacted 699 patients with SSc or Mixed Connective Tissue Disease (MCTD) to complete an anonymous survey. In total, 198 patients with SSc completed the survey consisting of questionnaires on sociodemographics, disease characteristics, quality of life and health care utilization. Descriptive statistics were used to describe demographic characteristics and health care use. Results: Most respondents were female (86.4%) with an average age of 58.1 years (range 29-85) and a mean time since diagnosis of 11.1 years (SD 9.5). The majority of the patients (65.2%) were diagnosed with limited SSc/CREST. Health care use is displayed in Table 1 . In the last 12 months, the majority of the patients (95%) had contact with at least one medical specialist, and two-third contacted at least one health professional. The median number of different health care providers contacted since the onset of SSc and in the last 12 months was 8 and 4, respectively. A median of 7 visits per year to medical specialists and 7.5 visits to health professionals were reported. Conclusions: Health care use in SSc is substantial, as is reflected in both the high number of visits to health care providers and the number of different health care providers. Due to the complexity of the disease and the high number of different health care providers patients might receive overlap in treatment or contradictory advices. Therefore, attention should also be given to coordination and communication among health care providers. References: Hudson M, Thombs BD, Steele R, Panopalis P, Newton E, Baron M, Canadian Scleroderma Research Group. Health-related quality of life in systemic sclerosis: a systematic review. Arthritis Rheum 2009; 61: 1112-20. Disclosure of Interest: None Declared